PEMBINAAN SEBAGAI UPAYA REHABILITASI SOSIAL PENGGUNA NAPZA (Studi pada Lapas Narkotika Klas IIA Sungguminasa Gowa) - Darwis . (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
Social rehabilitation process of drug users in terms of coaching in Lapas Narkotika (Narcotics Penitentiary) Class IIA Sungguminasa covered a) rehabilitation of social behavior which consists of mental and spiritual coaching, discipline, religious coaching, education, law enforcement, skills development, guidance and counseling, structured guidance and personality development, b) social rehabilitation in forms of legal actions such as remission and rewards or penalty against infringement, c) financial aspects concerning the operational cost of the penitentiary, and d) process of integration during mapeling (admission orientation), skills development and religious activities. On the other hand, the increasing number of inmate indicated that social rehabilitation programs in the narcotics penitentiary has not functioned optimally as a correctional institution. The process of social reintegration covers: a). prevention, b). therapeutic efforts, c). enforcement d). alternative efforts. Social reintegration undertaken in the Narcotics Penitentiary includes all parties ranging from officers, inmates and the public in order to prevent illicit trafficking or abuse of drugs in the penitentiary. Inhibiting factor in the development of the social rehabilitation efforts is the lack of infrastructure and human resources in specific field such as psychologist and counselor.Keywords: Coaching, Social Rehabilitation, Drug Users